EFEKTIVITAS KOMPETENSI MANAJERIAL KETUA PROGRAM KEAHLIAN DALAM MENINGKATKAN KEBERHASILAN PRAKTIK KERJA LAPANGAN DI SMK - Muryati, Sri; Ilham Fahmi; Saprialman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Industrial Revolution 4.0 demands vocational students to possess adaptive technical and soft skills. This study aims to determine the effect of the managerial competence of the Head of the Expertise Program on the success of Field Work Practice (PKL) for students of Automation and Office Management (OTKP) at SMK 2 PGRI Karawang. This research uses a quantitative approach with an explanatory survey method. The study population consisted of 160 students from class XI OTKP, with a sample of 62 students determined through the Slovin formula. Data were collected using questionnaires with a 4-point Likert scale, observations, and documentation. The analytical techniques applied included descriptive statistics, classical assumption tests, and simple linear regression. The findings indicate that the managerial competence of the Head of the Expertise Program, which includes dimensions such as integrity, communication, and decision-making, has a significant influence on the success of PKL. Effective management ensures industrial placement suitability, intensive mentoring, and the achievement of student work competencies. Thus, improving managerial competence is essential to optimizing the link and match between vocational education and industrial needs.